RURAL ROAD AND MARKETING OF AGRICULTURAL PRODUCE: A CASE STUDY OF KAJOLA LOCAL GOVERNMENT AREA OF OYO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
The transport system is fundamental to economic and social development of rural communities. The study examined the impact of road transportation system on the marketing of agricultural produce in Kajola local government area of Oyo state. Multi stage sampling technique was used to select one hundred and sixty (166) rural farmers for the study. Primary data were collected with the use of a pre-tested questionnaire and analyzed using descriptive and inferential statistics. Results revealed that 72.7% of the respondents were male, 69.5% were married with a mean age of 40.83years. Also, 91.4%, 89.8%, 87.5%, 79.7% and 76.6%, of the respondents produced maize, tomatoes, pepper, yam and cassava respectively while 21.9% produced cucumber. Furthermore, 60.2% of the farmers move their produce from the farm to the market through feeder roads using motorcycles due to the bad state of the roads. Respondents revealed that bad road networks bring about reduced quantity of farm produce leading to higher price. The result of the correlation analysis revealed that road transportation mode is significantly (p
Keywords: Transportation, Marketing, Rural road, Kajola